2023
DOI: 10.1007/s00520-023-08031-8
|View full text |Cite
|
Sign up to set email alerts
|

Latent class symptom profiles of colorectal cancer survivors with cancer-related cognitive impairment

Claire J. Han,
Leorey Saligan,
Adele Crouch
et al.

Abstract: Purpose. Colorectal cancer (CRC) survivors experience cancer-related cognitive impairment and cooccurring symptoms after cancer treatments. There has been little data to inform the risk factors of complex symptom phenotypes in CRC survivors.Objectives.To determine if subgroups of CRC survivors after cancer treatments could be identi ed based on the cognitive impairment and common co-occurring symptoms (depression, anxiety, sleep disturbance, fatigue, and pain); and to explore risk factors (sociodemographic and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This finding is in line with previous research on cancer that found that higher levels of fatigue, pain, and sleep disturbance were correlated with worse cognitive function. 7 , 9 Moreover, previous reports have confirmed the existence of subgroups of multiple psychoneurological symptoms and suggest inter-individual variability of symptom experience in cancer populations. 8 Notably, cognitive impairment and common co-occurring symptoms may share common biological mechanisms.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This finding is in line with previous research on cancer that found that higher levels of fatigue, pain, and sleep disturbance were correlated with worse cognitive function. 7 , 9 Moreover, previous reports have confirmed the existence of subgroups of multiple psychoneurological symptoms and suggest inter-individual variability of symptom experience in cancer populations. 8 Notably, cognitive impairment and common co-occurring symptoms may share common biological mechanisms.…”
Section: Discussionmentioning
confidence: 83%
“… 5 , 6 Research of symptom clusters from other cancer populations indicates robust associations between co-occurring symptoms (fatigue, sleep disturbances, pain, depression) and cognitive impairment and that patients with cognitive impairment experienced distinct co-occurring symptom profiles. 7 , 8 , 9 These symptoms are also prevalently reported among PC patients with cognitive impairment, especially following ADT. 6 , 10 However, exploring symptom clusters of cognitive impairment and common co-occurring symptoms remains poorly understood in PC patients undergoing ADT.…”
Section: Introductionmentioning
confidence: 97%
“…Some of these studies have primarily focused on diverse cancer populations, failing to account for the unique subpopulation differences within the symptom cluster of fatigue, pain, and sleep disturbance 10–12 . Studies have also emerged for specific subpopulations, such as breast, lung, and pediatric cancer, 13–15 that used LPA to classify patients into latent classes based on their unique experiences with some of the common co‐occurring symptoms during chemotherapy 16,17 . Notably, these studies have identified a subgroup of individuals with high‐symptom burden.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 , 12 Studies have also emerged for specific subpopulations, such as breast, lung, and pediatric cancer, 13 , 14 , 15 that used LPA to classify patients into latent classes based on their unique experiences with some of the common co‐occurring symptoms during chemotherapy. 16 , 17 Notably, these studies have identified a subgroup of individuals with high‐symptom burden. This subgroup may represent a high‐risk category with a distinct symptom phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…The latent class analysis is bene cial for symptom research where data often include heterogeneous groups of individuals with cancer experiencing multiple symptoms, and for identifying distinct subgroups of patients based on their symptoms [10,11]. Although latent class modeling was used in a few studies in cancer survivors to identify symptom clusters [12][13][14], no published symptom cluster study using latent class analysis has compared distinct symptom subgroups across different cancer types. Comprehensive and representative samples of cancer survivors using the latent class approach in conjunction with well-validated and reliable patient-reported outcomes might be helpful in clarifying how subgroups of survivors may differ across different cancer diagnosis based on a symptom cluster.…”
Section: Introductionmentioning
confidence: 99%